124k views
4 votes
5x-2y=-6 3x-4y = -26​

1 Answer

4 votes

For this case we must solve the following system of equations:


5x-2y = -6\\3x-4y = -26

We multiply the first equation by -2:


-10x + 4y = 12

We add the new equation with the second one:


-10x + 3x + 4y-4y = 12-26

We have different signs subtracted and the sign of the major is placed:


-7x = -14\\x = \frac {-14} {- 7}\\x = 2

Now we find the value of the variable "y":


3x-4y = -26\\3 (2) -4y = -26\\6-4y = -26\\-4y = -26-6\\-4y = -32\\y = \frac {-32} {- 4}\\y = 8

Thus, the solution of the system is given by:


(x, y) :( 2,8)

Answer:


(x, y) :( 2,8)

User Duffymo
by
5.6k points